Planetary Sciences, Geodynamics, Impacts, Mass Extinctions, and Evolution: Developments and Interconnections - Jaime Urrutia-Fucugauchi; Ligia Pérez-Cruz (International Journal of Geophysics)
Research frontiers in geophysics are being expanded, with development of new fields resulting from technological advances such as the Earth observation satellite network, global positioning system, high pressure-temperature physics, tomographic methods, and big data computing. Planetary missions and enhanced exoplanets detection capabilities, with discovery of a wide range of exoplanets and multiple systems, have renewed attention to models of planetary system formation and planet’s characteristics, Earth’s interior, and geodynamics, highlighting the need to better understand the Earth system, processes, and spatio-temporal scales. Here we review the emerging interconnections resulting from advances in planetary sciences, geodynamics, high pressure-temperature physics, meteorite impacts, and mass extinctions.